Marginal Groups in the Labour Market: Those Refused Unemployment Benefits (Szociológiai Szemle, 2024)
Statistics compiled by the National Jobs Centre show that a certain percentage of people eligible for unemployment benefits are excluded from the system. The official explanation is that „they do not cooperate properly with the Jobs Centre”. One of the goals of my research was to determine just what ‘not properly cooperating’ actually means — to find out why people are denied benefits which would otherwise keep them above the poverty line. My intention is to examine the manner in which the Jobs Centre deals with its clients; what happens to an individual or a family as a result of the elimination of benefits; and how people are able to cope with exclusion from benefits.